2018
DOI: 10.1371/journal.pone.0203187
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an acrylic resin after immersion in antiseptic soaps: Low-cost, easy-access procedure for the prevention of denture stomatitis

Abstract: Denture stomatitis triggered by Candida species requires better preventive measures. This study evaluated the physical and biological properties of a denture base acrylic resin after immersion in antiseptic soaps. Acrylic resin specimens were prepared and stored in distinct solutions for 0, 7, 14, 21, and 28 days. The solutions were as follows: DW: distilled water at 37°C (control group); DS: cycles of daily immersion in Dettol soap for 8 hours at room temperature, followed by immersion in distilled water for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 49 publications
4
36
1
3
Order By: Relevance
“…These MIC values are lower than those reported for most of the ubiquitous phyto-constituents in the literature [40,41]. Moreover, the disinfectant potency of the G. cambogia extracts was comparable to that of the commercial disinfectant Lifebuoy ® soap used as reference [23]. Although the disinfectant capacity of an obicure tea extract containing green tea, G. cambogia, ginger and pepirene was determined from zone of inhibition as well as by totally incubating in a broth and visualizing the presence or absence of turbidity [42], to the best of our knowledge, this is the first report on the evaluation of disinfectant potency of G. cambogia extract on different surfaces that might correlate to smooth and rough surfaces in hospital settings.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These MIC values are lower than those reported for most of the ubiquitous phyto-constituents in the literature [40,41]. Moreover, the disinfectant potency of the G. cambogia extracts was comparable to that of the commercial disinfectant Lifebuoy ® soap used as reference [23]. Although the disinfectant capacity of an obicure tea extract containing green tea, G. cambogia, ginger and pepirene was determined from zone of inhibition as well as by totally incubating in a broth and visualizing the presence or absence of turbidity [42], to the best of our knowledge, this is the first report on the evaluation of disinfectant potency of G. cambogia extract on different surfaces that might correlate to smooth and rough surfaces in hospital settings.…”
Section: Discussioncontrasting
confidence: 53%
“…The disinfectant activity was assessed after treating smooth and rough surfaces with different plant extracts; the disinfectant Lifebuoy ® soap (containing silver as active ingredient [23]) was used as the reference. As shown in Table 4, a prominent disinfectant efficiency was observed especially with the n-hexane extract of G. cambogia against all the tested microorganisms on both types of surfaces.…”
Section: Disinfectant Activitymentioning
confidence: 99%
“…An alternative of providing cost control in prosthesis hygiene assistance was pointed out in a study with the use of antiseptic soaps. In the study that aimed to assess the physical and biological properties of an acrylic resin, based on prostheses, after immersion in antiseptic soaps, it was successful in controlling Candida albicans, which can be a cheap and easy procedure to prevent stomatitis by dental prosthesis (27) .…”
Section: Discussionmentioning
confidence: 99%
“…13 Several studies reported some changes related to the strength, hardness, color, and roughness of the acrylic resin materials following disinfection. 9,11,38 Another recent study found that the short-term acrylic resin disinfection did not affect the flexural strength, surface roughness, and the color of different commercially available orthodontic acrylic resins. 33 These uncertain outcomes could be related to the type of the material, the type of disinfectant, the followed protocol, and disinfection duration.…”
Section: Discussionmentioning
confidence: 99%
“…Solutions applied for intended disinfection should preserve their physical and mechanical properties, not compromising the surface integrity of the material. 9 The extent of the roughness of an orthodontic appliance can influence the biofilm attachment, which might accelerate the colonization of microorganisms and alter the appliance’s color. 10 This condition is critical as orthodontic appliances must have a smooth surface to prevent the adhesion and colonization of oral microbes.…”
Section: Introductionmentioning
confidence: 99%